SOCIOECONOMIC, EPIDEMIOLOGICAL AND LABORAL CHARACTERIZATION OF CONTRACT WORKERS OF A PUBLIC UNIVERSITY - Nayara Pires Nadaleti; Jefferson Felipe Ribeiro; Poliana Martins Ferreira; Denismar Alves Nogueira; Adriana Olimpia Barbosa Felipe; Fábio de Souza Terra (Universidade Federal do Paraná, 2018)
Objective: to analyze the socioeconomic, epidemiological and work characteristics of contract workers of a public university in the south of Minas Gerais. Method: quantitative, descriptive and cross-sectional study, performed between December 2016 and February 2017 with 316 contract workers. A characterization questionnaire was used for the data collection and descriptive statistics for the data analysis. Results: the profile found was of female workers (54.4%), in the 30 to 39 years age group (31.3%), married/with partner (58.2%), with children (69.3%), with a family income from 1.5 to 3.5 minimum wages (51.6%), that did not practice physical activities (42.7%), did not have chronic diseases (69.9%), had performed contract work for up to 10 years (81.3%), with a workload of 44 hours per week (84.4%) and that had worked in the current institution for less than four years (63.9%). Conclusion: identifying the profile of these workers allows the adoption of promotion and prevention strategies capable of improving the quality of the work and social life.